Cost and health care resource use associated with noncompliance with oral bisphosphonate therapy: an analysis using Danish health registries. Issue 12 (December 2016) - Kjellberg, J.; Jorgensen, A.; Vestergaard, P.; Ibsen, R.; Gerstoft, F.; Modi, A.
Abstract Summary We estimated the rate of compliance with oral bisphosphonates among Danish women and examined its association with health care resource use and cost. Approximately 30 % of Danish females aged >55 who take bisphosphonates are noncompliant, and noncompliance is significantly associated with increased health care resource use and cost. Introduction Two objectives of this study were to estimate the rate of oral bisphosphonate compliance among Danish women and to examine the association of noncompliance with health care resource use and cost. Methods Women ≥55 with an index prescription claim for an oral bisphosphonate were identified from Danish national health registries between 2003 and 2008. Compliance was measured as the medication possession ratio (MPR) during the first 12 months post-index. Cost and health care resource use were collected for the following 12 months. Results Among the 38, 234 women meeting the study inclusion criteria, 29.9 % were noncompliant (MPR <70 %). Younger age was associated with higher odds of compliance (OR [95 % CI] 1.22 [1.15–1.29] for ages 55–64 and 1.18 [1.12–1.24] for ages 65–74; reference age group ≥75 years). Rates of all-cause health care resource use were significantly higher in noncompliant subjects: 28.9 versus 23.0 % had inpatient admissions, 16.5 versus 13.0 % had emergency room visits, and 48.7 versus 43.3 % used outpatient services (P < 0.001 for all comparisons). The total mean (SD) all-cause cost per patient (excluding office visits) was €626 (2344) and €4178 (7854), respectively. The mean (SD) osteoporosis-related cost per patient (excluding office visits) was €572 (2085) and €754 (2857) for compliant and non-compliant subjects, respectively. The compliant subjects accrued significantly lower all-cause and OP-related cost than noncompliant subjects, regardless of whether the total cost or medical cost only was considered. Conclusions Approximately 30 % of Danish females aged 55 or older who take bisphosphonates are noncompliant. Noncompliance is significantly associated with increased health care resource use and cost.